2009
DOI: 10.1159/000247001
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Placebo-Controlled, Randomized Phase II Pilot Study to Investigate the Potential Efficacy of the Traditional Chinese Medicine Neuroaid (MLC 601) in Enhancing Recovery after Stroke (TIERS)

Abstract: Background and Objective: Previous clinical studies have shown that Neuroaid (MLC 601) may be beneficial in post-stroke rehabilitation. Our aim was to investigate the efficacy of Neuroaid on motor recovery in ischemic stroke patients using rehabilitation endpoints in accordance with the International Conference on Harmonization/Good Clinical Practice guidelines, in order to provide predictive information for further larger trials. Methods:This is a phase II double-blind, placebo-controlled pilot study of 40 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…Another study was identified through personal contact of the author (C.C.). In total, 5 studies were short-listed for full text evaluation [7,14,15,16,17]. Of these, 1 was the previous systematic review of 2 unpublished Chinese trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study was identified through personal contact of the author (C.C.). In total, 5 studies were short-listed for full text evaluation [7,14,15,16,17]. Of these, 1 was the previous systematic review of 2 unpublished Chinese trials.…”
Section: Resultsmentioning
confidence: 99%
“…All 6 included trials compared MLC601 to placebo [14,15,16] or another treatment, i.e. piracetam [17] and Buchang [7].…”
Section: Resultsmentioning
confidence: 99%
“…Because previous studies on MLC601 suggested a benefit in nonacute ischemic stroke patients, [11][12][13][14][15][16][17] the time window of 72 hours was chosen for this study in an attempt to test both the neuroprotective and neurorestorative properties of MLC601.…”
Section: Discussionmentioning
confidence: 99%
“…11 More studies have since been published assessing the benefit and safety of MLC601 in nonacute stroke patients using different clinical outcomes. [12][13][14][15][16][17][18][19] Although most patients experience some spontaneous recovery in the months after a stroke, the degree and timing of recovery are variable. Improving functional outcomes through specific interventions is a relatively unexplored area of great public health potential.…”
Section: August 2013mentioning
confidence: 99%
See 1 more Smart Citation